Definition of men’s science and its place among science - Kazim, Ali Saleh Abdullah; Khalil, Ali Nihad (Al-Adab Journal, 2020)
The science of men is a science looking at the conditions of the narrator to talk about the infallible (peace be upon him) of the fact that his description tapes acceptance of his experience or not, and the importance of men’s science lies in the recognition of the conditions of the narrator, in terms of being trust or not trust, or being fair or unfair , Or Mamdouh or vilified, or unknown, or neglected, and other qualities that characterize the narrator to talk, and full access to his life and his pupils, elders and classes belonging to them, and other things on which the acceptance of the news of the jurisprudent deducted from the legal provisions, and the subject of men’s knowledge is The names of the narrators to talk, the questions of this science is to search for the conditions of the narrator interrelated With the acceptance of the incoming news such as document and control and class and doctrine and so on the conditions of the narrator to talk that has income as news or response, and the purpose of full knowledge of who accepts his experience or who is speaking, that is, to stand on the conditions of the narrator in terms of document narrator or not and then discrimination for the acceptable Otherwise, the science of men is the basic basis on which the hardworking in the knowledge of the provisions of Sharia.